Trends and predictions of maternal sepsis and other maternal infections among women of childbearing age: a systematic analysis for the global burden of disease study 2019 - Qian, Hang; Shang, Weifeng; Zhang, Sheng; Pan, Xiaojun; Huang, Sisi; Li, Hui; Wen, Zhenliang; Liu, Jiao; Chen, Dechang (Frontiers in Public Health, 2024)
Background Maternal sepsis and other maternal infections (MSMIs) are major public health concerns worldwide. However, comprehensive data on their global burden and evolving trends remain sparse. This study aims to explore the epidemiological trends of MSMIs in women of childbearing age (WCBA) from 1990 to 2019, investigate the relationship between disease burden and age, period, and birth cohorts, and then provide a prediction of MSMIs incidence and deaths. Methods The estimates and 95% uncertainty intervals (UIs) for the incidence and death number of MSMIs in seven age groups (15–19, 20–24, 25–29, 30–34, 35–39, 40–44, 45–49 years) were obtained from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2019. The age-standardized incidence and mortality rates of MSMIs in WCBA were estimated utilizing the age standardization by direct method. Joinpoint regression analysis was employed to investigate the changing trends of age-standardized incidence and mortality rates from 1990 to 2019. Age-period-cohort analysis was utilized to estimate the independent effects of age, period, and birth cohorts. Furthermore, a Nordpred age-period-cohort analysis was implemented to predict the global epidemiological trends through 2044. Results In 2019, the estimated global age-standardized incidence and mortality rates of MSMIs in WCBA were 1072.90 (95% UI: 725.93 to 1483.46) and 0.86 (95% UI: 0.69 to 1.05), respectively. The highest disease burden existed in the African Region. From 1990 to 2019, the estimated global age-standardized incidence and mortality rates of MSMIs (AAPC: -1.32, 95% CI: −1.34 to −1.30; AAPC: -3.39, 95% CI: −4.28 to −2.48) in WCBA both demonstrated significant declining trends. The changing trends varied significantly across 6 regions and 204 countries. The effects of age, period, and cohort on incidence and mortality rates differed. From 2020 to 2044, the global age-standardized incidence rate of MSMIs in WCBA was predicted to decrease whereas the case number increases slowly. Conclusion The global trends in MSMIs incidence and mortality generally showed a decline with considerable heterogeneity, indicating both the effectiveness and unevenness of global management of MSMIs. Moreover, the predicted increased case number highlights prominent challenges in the control of MSMIs.